SELF EFFICACY LOCUS OF CONTROL DAN KOMPETENSI SERTA PENGARUHNYA KEPADA KINERJA (Studi Kasus Pengusaha UMKM di Kecamatan Darmaraja, Sumedang Barat - Indonesia) - Chairul Hakim; Komarudin Komarudin (STMIK Mardira Indonesia, Bandung, 2020)
Competency and individual characteristics such as self-efficacy and locus of control can determine an entrepeneur's success in managing its business. This study examined the effects of self-efficacy, locus of control and competency on small medium enterprises performance in Darmaraja-West Sumedang. This study used survey research design and respondents were SMEs entrepreneurs located in Darmaraja-West Sumedang (N = 236). Result of the multiple regression analysis showed that competency had a significant and positive effects on SMEs performance. self-efficacy had a significant and positif effect on Competency. and locus of control had a significant effect on Competency. Implications for future research and practice were discussed. Keywords: Self-efficacy, Locus of Control, Competency, Perfomance, SMEsDOI : http://doi.org/10.5281/zenodo.3928948